Peri-implantitis in partially edentulous patients: association with inadequate plaque control - Serino, Giovanni; Ström, Christer (Clinical oral implants research, 2009)
Objective: The aim of the present study was to describe some clinical periodontal features of partially edentulous patients referred for the treatment of peri‐implantitis. Material and methods: The 23 subjects involved in this study were selected from consecutive patients referred to the department of Periodontology Södra Älvsborgs Hospital, Borås, Sweden, for treatment of peri‐implantitis during 2006. The patients had clinical signs of peri‐implantitis around one or more dental implants (i.e.≥6 mm pockets, bleeding on pockets and/or pus and radiographic images of bone loss to≥3 threads of the implants) and remaining teeth in the same and/or opposite jaw. The following clinical variables were recorded: Plaque Index (PI), Gingival Bleeding Index (GBI) Probing Pocket Depth (PPD), Access/capability to oral hygiene at implant site (yes/no), Function Time. The patients were categorized in the following sub‐groups: Periodontitis/No periodontitis, Bone loss/No bone loss at teeth, Smoker/Non‐smokers. Results: Out of the 23 patients, the majority (13) had minimal bone loss at teeth and no current periodontitis; 5 had bone loss at teeth exceeding 1/3 of the length of the root but not current periodontitis and only 5 had current periodontitis. Six patients were smokers (i.e. smoking more than 10 cig/day). The site level analysis showed that only 17 (6%) of the 281 teeth present had ≥1 pocket of ≥6mm, compared to 58 (53%) of the total 109 implants (28 ITI® and 81 Brånemark®); 74% of the implants had no accessibility to proper oral hygiene. High proportion of implants with diagnosis of peri‐implantitis were associated with no accessibility/capability for appropriate oral hygiene measures, while accessibility/capability was rarely associated with peri‐implantitis. Indeed 48% of the implants presenting peri‐implantitis were those with no accessibility/capability for proper oral hygiene (65% positive predict value) with respect to 4% of the implants with accessibility/capability (82% negative predict value). Conclusion: The results of the study indicate that local factors such as accessibility for oral hygiene at the implant sites seems to be related to the presence or absence of peri‐implantitis. Peri‐implantitis was a frequent finding in subjects having signs of minimal loss of supporting bone around the remaining natural dentition and no signs of presence of periodontitis (i.e. presence of periodontal pockets of ≥6 mm at natural teeth). Only 6 of the examinated subjects were smokers. In view of these results we should like to stress the importance of giving proper oral hygiene instructions to the patients who are rehabilitated with dental implant and of proper prosthetic constructions that allow accessibility for oral hygiene around implants.